Unexpected impairment of TNF-α-induced maturation of human dendritic cells in vitro by IL-4. Issue 1 (December 2016) - Chabot, Valérie; Martin, Laurence; Meley, Daniel; Sensebé, Luc; Baron, Christophe; Lebranchu, Yvon; Dehaut, Frédéric; Velge-Roussel, Florence
Abstract Background An efficient strategy for programing dendritic cells (DCs) for cancer immunotherapy is the optimization of their maturation so that they can efficiently stimulate cancer-specific T cell responses. Interleukin (IL)-4 has appeared as an essential cytokine, widely used in vitro with granulocyte macrophage-colony stimulating factor (GM-CSF) to differentiate monocytes into immature DCs (iDC) and to prevent macrophage formation. Conflicting data have been published regarding the effect of IL-4 on functional DC maturation. To further understand IL-4's effects on DC maturation and function in vitro, we choose the most commonly used maturation factor tumor necrosis factor (TNF)-α. Methods Human monocyte-derived iDC were treated for 48 h with GM-CSF and TNF-α in the presence (IL-4+ -DC) or absence (IL-4− -DC) of IL-4 and functions of both DC populations were compared. Results On mixed lymphocyte reaction assay, IL-4+ -DC were less potent than IL-4− -DC at inducing the proliferation of allogeneic CD4+ T cells and the proportion of activated T cells expressing CD69 and/or CD25 was smaller. Interleukin-4 reduced the cell-surface expression of TNF-α-induced DC maturation markers CD83, CD86, HLA-DR and CD25 and generated a heterogeneous population of DCs. IL-4+ -DC secreted less IL-12 and more IL-10 than IL-4− -DC following activation by soluble CD40L, and IL-4+ -DC-activated T cells secreted lesser amounts of T helper (Th) 1 cytokines (IL-2 and interferon-γ). Importantly, IL-4 impaired the in vitro migratory capacity of DCs in response to CCL21 and CCL19 chemokines. This effect was related to reduced expression of CCR7 at both mRNA and protein levels. Conclusion Interleukin-4 used with GM-CSF and TNF-α during the maturation of DCs in vitro impaired DC functions and disturbed the maturation effect of TNF-α. Finally, our study reinforces the view that the quality of the DC maturation stimulus, which regulates DC migration and cytokine production, may be a decisive feature of the immunogenicity of DCs.